ANALISA TARIF INDONESIAN-CASE BASED GROUPS (INA-CBGs) STROKE ISKEMIK SEBELUM DAN SETELAH IMPLEMENTASI PERATURAN MENTERI KESEHATAN NOMOR 3 TAHUN 2023 - Berlin, Opel; Merryn, Kenny; Susan, Dewie (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Introduction: Stroke is a catastrophic disease with the third highest cost burden in Indonesia. The national health insurance scheme implemented until now is Indonesian-Case Based Groups (INA-CBGs). In response to inflation and the mismatch between hospital costs and INA-CBGs rates, the government has adjusted the INA-CBGs rates through Minister of Health (MOH) Regulation number 3 of 2023.Aim: This study aims to compare hospital costs with INA-CBGs rates before and after the implementation of Minister of Health Regulation number 3 of 2023 in hospitalized ischemic stroke patients.Methods: This analytical observational study was conducted on ischemic stroke patients with the INA-CBGs code G-4-14-x who were hospitalized in a type D private hospital in South Sumatra. Data was collected retrospectively from October 2020 to January 2024.Results: The most significant independent variable for hospital costs’ variation was length of stay (p = 0.000). There was an insignificant negative difference between hospital costs and INA-CBGs rates before and after the implementation of MOH Regulation number 3 of 2023 (- Rp. 1,013,529.17 vs. - Rp. 921,871.43; p = 0.113). The Class III – mild group was the only group that had significantly reduced the negative difference after the implementation of MOH Regulation number 3 of 2023 (- Rp 1.523.590,00 vs. – Rp 606.087,50; p = 0.026), but there was still a negative difference both before and after implementation.Discussion: The INA-CBGs rate adjustment is insufficient to cover ischemic stroke patients hospitalized in Type D private hospitals. Further research is needed with a larger sample size and conducted in hospitals of various types and regions.Keywords: Hospital costs, INA-CBGs rates, Ischemic stroke